Association between hearing loss and hypertension in non ear infection patients in Universitas Gadjah Mada Academic Hospital - Anton Sony Wibowo; Herfis Avidati; Sulis Ernawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Hearing loss is a common occurrence that can decrease productivity and quality of life. The incidence of hearing loss is often experienced by adults due to several factors, and one influencing factor is cardiovascular disease. Hypertension is known to have an effect on decreasing inner ear vascularization that will result in hearing loss. The objective of this study was to evaluate the association of hearing loss and hypertension in non-ear infection patients. This case-control study recruited subjects who underwent audiometric examination at the Universitas Gadjah Mada Academic Hospital, Yogyakarta, from June 2018 - July 2019. Hypertension was determined based on the results of blood pressure examination based on JNC 8 criteria. Hearing threshold value was taken from pure tone audiometry. The association of hypertension with hearing loss was analysed in each group and between study groups. Sixty patients who underwent audiometric examination divided into two groups with 30 patients in each group were involved in this study. There was a significant relationship between hypertension and hearing loss (OR=13.1; 95%CI: 3.8-45.0; p= 0.001). Hypertension acts as a variable that significantly affects the incidence of hearing loss. Patients with hypertension have a greater risk of hearing loss compared to patients without hypertension.